Special papers74-year-old man with left main and carotid artery disease – how life can change plans - Kübler, Piotr; Ilnicki, Dawid; Telichowski, Artur; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
An unexpected incident or rapid deterioration of a patient’s condition may require optimal adaptation of the treatment to the current state of the patient. We present a case of a 74-year-old man with significant left main coronary artery stenosis and tight stenoses of both carotid arteries. The case was initially qualified for bypass grafting with accompanying carotid artery endarterectomy, but an unexpected accident changed our way of treatment. Three days after angiography the patient suffered an ischemic stroke. We held a multidisciplinary meeting of the “Neuro-Vascular-Heart Team” and decided to treat the patient percutaneously.